PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS TEORI BELAJAR BRUNER PADA SISWA KELAS IV SDN 40/VI: PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS TEORI BELAJAR BRUNER PADA SISWA KELAS IV SDN 40/VI - nurlav avana (LPPM Universitas Muhammadiyah Muara Bungo, 2021)
The formulation of the problem is how to apply a realistic Mathematics learning model based on Bruner learning theory in improving the process and results of Mathematics learning in grade IV SDN 40 / VI Rantau Panjang. The purpose of this research is to describe and know the application of realistic Mathematics learning model based on the theory of learning bruner in improving the process and results of learning Mathematics in grade IV. This type of research used in this study is class action research (PTK). This research consists of 2 cycles, each cycle is carried out through 4 stages, namely: planning, action, observation and reflection and each cycle consists of 2 meetings. The subject of this research is 24 people, 16 female students and 8 male students. Data collection techniques are observation , tests and documentation. The results of the study can be explained as follows: (1) the application of realistic mathematics learning model based on the theory of learning bruner seen from the observation sheet that is cycle I of the teacher aspect with an average score of 80.6% and the aspect of students with an average score of 64.55% while in cycle II there is an increase from the teacher aspect with an average score of 90.625% and the aspect of students with an average score of 76.99% who have achieved indicators of success.